2018
DOI: 10.1167/iovs.18-24432
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trabodenoson in a Mouse Keratoconjunctivitis Sicca (KCS) Model for Dry-Eye Syndrome

Abstract: Topical ocular delivery of trabodenoson significantly improves the clinical and histopathological signs associated with dry-eye disease in mice. This improvement appears to be related to anti-inflammatory effects from targeting adenosine signaling and represents a novel therapeutic approach to develop for the management of dry-eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…Neither drug was able to increase the number of conjunctival goblet cells (Fig. 5C, D), in agreement with previous reports [32].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Neither drug was able to increase the number of conjunctival goblet cells (Fig. 5C, D), in agreement with previous reports [32].…”
Section: Discussionsupporting
confidence: 93%
“…Our mouse model for DED is based on a well-established paradigm that employs low-humidity air flow and concurrent scopolamine administration to induce DED in wild-type mice [36]. The model and its quantitative readouts used to determine DED severity were published by us previously [32] and are of similar magnitude to those reported by us and others using a desiccating stress/ scopolamine model to induce DED in mice [32,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting tear secretion by systemic administration of the muscarinic cholinergic antagonist scopolamine produced keratoconjunctivitis sicca that mimics human dry eye. This scopolamine-induced dry eye model is commonly used animal model in DED research [22,[24][25][26][27]. We demonstrated that the oxidation product 8-OHdG accumulated in the corneal epithelial cells of this model.…”
Section: Plos Onementioning
confidence: 74%